Association between cardiac biomarkers and LVEF after congenital heart disease surgery in infants - Mo, Yuxiao; Feng, Qing; Wang, Xia; Feng, Shuwen; Wei, Cong; Zou, Minghui; Liu, Jinping; Zheng, Junwen; Zhao, Dongchi (Frontiers in Pediatrics, 2025)
ObjectiveCardiac biomarkers are widely used to evaluate postoperative myocardial injury, but studies on their relationship with cardiac function in pediatrics are limited. This study aimed to characterize the dynamic changes of cardiac biomarkers after congenital heart disease (CHD) surgery in patients aged 0–3 years and assess their correlation with cardiac function.MethodsWe retrospectively enrolled 63 pediatric patients (0–3 years) who underwent CHD surgery at Zhongnan Hospital between January 2021 and June 2024. Biomarkers and left ventricular ejection fraction (LVEF) were measured preoperatively and postoperatively within 1 week. The associations between the biomarkers and LVEF were analyzed. Receiver operating characteristic (ROC) curves were used to assess the predictive accuracy of the biomarkers for cardiac dysfunction, composite complications, and early mortality.ResultsBiomarker levels peaked on postoperative day (POD) 1 and declined to near-baseline levels within 1 week. LVEF decreased initially and then gradually recovered to near preoperative levels by POD 4–7. LVEF on POD 1 negatively correlated with the peak high-sensitivity troponin I (hs-TnI) and creatine kinase–MB (CK-MB) levels. The ROC analysis showed that hs-TnI and CK-MB had good predictive power for cardiac dysfunction (AUC = 0.818 and 0.828) and composite complications (AUC = 0.736 and 0.745), but limited value for early mortality (AUC = 0.665).ConclusionHs-TnI and CK-MB are key biomarkers that reflect the relationship between myocardial injury and cardiac function recovery after CHD surgery in pediatric patients aged 0–3 years. Their peak postoperative levels can predict cardiac function recovery and composite complications.